2020
DOI: 10.1002/adma.202003983
|View full text |Cite
|
Sign up to set email alerts
|

Dopant‐Driven Positive Reinforcement in Ex‐Solution Process: New Strategy to Develop Highly Capable and Durable Catalytic Materials

Abstract: Supported catalysts, in which metal nanoparticles (NPs) are distributed on oxide supports, are widely used in a variety of industrial processes, including in catalysis, [1] sensing, [2] and renewable energy. [3] To improve the reactivity, costeffectiveness, and durability of catalysts, decreasing their particle size to ensure uniform dispersion on the support and to suppress their aggregation during operation, particularly at high temperatures (>500 °C) is of utmost importance. Thus far, not only conventional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 30 publications
2
27
0
Order By: Relevance
“…Small published by Wiley-VCH GmbH convert CH 4 using CO 2 [155] and the other two on CO oxidation. [156,157] In all cases, it is demonstrated that the improved catalytic activity of the material was induced after the emergence of the Ir nanoparticles on the surface. In the former case this was shown to be due to the particles' ability to catalyze the cleavage of the CH bond in CH 4 with high coking resistance.…”
Section: (22 Of 27)mentioning
confidence: 89%
See 2 more Smart Citations
“…Small published by Wiley-VCH GmbH convert CH 4 using CO 2 [155] and the other two on CO oxidation. [156,157] In all cases, it is demonstrated that the improved catalytic activity of the material was induced after the emergence of the Ir nanoparticles on the surface. In the former case this was shown to be due to the particles' ability to catalyze the cleavage of the CH bond in CH 4 with high coking resistance.…”
Section: (22 Of 27)mentioning
confidence: 89%
“…At the same time exsolution offers exceptional control over particle characteristics (size, population, and distribution), which allows for fine tuning of the activity and the selectivity of processes that employ exsolved materials. [5,16] Due to the combination of activity, durability, as well as compositional, structural, and functional tunability, the application of exsolved materials has proven to be [5,[8][9][10][11]15,16,22,23,26,40,125,140,157] In the exsolution method, illustrated schematically in Figure 1a, the active (i.e., exsolvable) elements are substituted in a host lattice under oxidizing conditions, forming an oxide solid solution, and released as metallic particles upon exposure to reducing conditions, leaving behind the host lattice as support. There are thus a number of key processes fundamental to exsolution, as schematically illustrated in Figure 1b: formation of a solid solution phase, exposure to reducing conditions to provide the driving force for the phase segregation, nucleation and growth of the exsolved phase, diffusion of ions, and oxide ions, and electrons across the host lattice to fuel the nucleation and growth process (generally shuttling between the bulk and the surface, but also locally if this occurs within the bulk or near-surface).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7,8] In addition, thermal degradation of the sensing layer and the agglomeration of metal catalysts could both degrade the sensor performance, compromising its reliability in long-term operations. [9,10] Moreover, the brittleness of oxides limits the scope of utilization from flexible and wearable devices, which are key aspects for consumer applications in the immediate future. To this end, it is necessary to develop an effective design strategy which integrates nanostructured oxide layers with a flexible polymer substrate as an underlying layer [11,12] and a molecular sieving layer for selective gas filtration.…”
Section: Doi: 101002/adma202105869mentioning
confidence: 99%
“…On the basis of this discovery, Jang et al recently demonstrated a highly stable chemiresistive sensor which employs Ir as the exsolution catalyst on two-dimensional (2D) WO 3 nanosheets (NSs). 152 Specifically, the substitution of W with Ir led to an improved reducibility of the WO 3 host oxide, enabling the exsolution at significantly low temperatures (300 °C) as compared to those in other approaches. As shown in Figure 21a, the extraction of Ir nanoparticles from the host WO 3 at a low temperature was accelerated due to the phase transformation of the host WO 3 from monoclinic to tetragonal WO 3 and WO 2.9 phases during the reduction process.…”
Section: Other Opportunitiesmentioning
confidence: 99%